The Kind of Hedonism Life Styles Found in John Hughes’s The Home Alone Movie (1990) - Pribadi, Tinto Sakti; Prastiwi, Yeny (Language Circle: Journal of Language and Literature, 2024)
This research was conducted to analyze the types of hedonism that exist in the 1990 Home Alone film. Home Alone itself is not even a film that focuses on luxury, this film focuses on a situation where a child lives alone at home and is terrorized by a group of robbers who want the priceless stuffs in the house. Several scene on this movie feature scenes related to lifestyle. One of them is the hedon lifestyle. It also includes experiences that are intrinsically valuable, such as reading a good book. Hedonic lifestyles can be divided into 2 (two), as follows: (a) Egoistic Hedonism and (b) Universal Hedonism. The method of this study is descriptive and qualitative. The object of this study is to analyze kind of the hedonism life style aspect in this movie. The author collects data primary data by watching scenes in the filmHome Alone to know and understand what the meaning of scenes shown in the film. In analyzing data, author use the literature study method which requires author to find and analyze research or journals from various sources. The results of the data there are has found kind of the Hedonism like eating style, house style, fashion style, pet option, and vacation style. All of them has divided into 2 kind of hedonism type egoistic and universal hedonism. By studying the case of hedonism in the film Home Alone 1990, it is hoped that readers will be able to choose wisely in seeking satisfaction/pleasure in life. So as to avoid the bad impacts of hedonism.